Effect of the CDC light trap on control of nocturnal mosquitoes in coastal Samut Songkhram Province, Thailand - TANAWAT CHAIPHONGPACHARA; SEDTHAPONG LAOJUN; CHAEKKI KUNPHICHAYADECHA (Biodiversitas Journal of Biological Diversity, 2018)
Chaiphongpachara T, Laojun S, Kunphichayadecha C. 2018. Effect of the CDC light trap on control of nocturnal mosquitoes in coastal Samut Songkhram Province, Thailand. Biodiversitas 19: 1750-1754. This study aimed to investigate the effect of CDC light trap on mosquito control and to study the relationship between this effect and weather factors in coastal areas (2 and 4 km from the sea) of Samut Songkhram Province, Thailand. We conducted a field test by trapping for 30 consecutive days from September to October 2017. The trap was hung at a height of 1.5 m and was 50 m away from a house. A total of 2963 adult female mosquitoes of 4 species belonging to 2 genera were trapped, including Anopheles epiroticus Linton & Harbach, Culex quinquefasciatus Say, Cx. sitiens Wiedmann and Cx. gelidus Theobald. The trapping rate of the CDC light trap set up 2 km from the sea was 85.70±73.81 adult mosquitoes per night. Meanwhile, at the location 4 km from the sea, the trap collected 13.07±11.40 adult mosquitoes per night. Comparing the numbers of mosquitoes captured by the CDC light trap between these two sites, there was a significant difference at p < 0.05. This study shows that the CDC light trap can be used for effective control of mosquitoes in coastal areas of Samut Songkhram Province, Thailand, especially Cx. sitiens, a filariasis vector.